COMPLIANCE ACADEMIC INTEGRITY LEARNING ACHIEVEMENTS OF EDUCATIONAL APPLICANTS IN THE PROCESS OF DISTANCE LEARNING - Nalyvaiko, Oleksii; Kalistova, Olena; Poliakov, Danylo (Educological discourse, 2020)
This article deals with the problem of respect for academic integrity. The relevance of this research consists in the quarantine measures, conducted be the Ukrainian government, in other words students could not attend all the classes in person. So that created an interesting problem, laying in the issues of respect for academic integrity. It has been analyzed and discussed by the authors. They also have defined and described the meaning of such concepts as ‘respect for academic integrity’, ‘distance learning’ and ‘e-learning’. It is specially noted main differences between distance learning and e-learning. The academic literature on this topic is analyzed and described in short. Data are given about the poll conducted among the students of V. N. Karazin Kharkiv National University on GoogleForms. The authors prepared ten questions related to respect for academic integrity during distance learning. The survey deals with key issues of respect for academic integrity problems as software and hardware of classes, during work in class, doing homework and term tests, evaluation of the effectiveness of methods of control, main reasons of disrespect for academic integrity and influence of that. Conclusions are drawn about main issues of distance learning, so we provided a reader with possible ways to cope with them. Recommendations are given for teachers and officials. The authors recommended to use some additional applications to control the students’ behavior during classes and doing tests, to conduct teacher training to deal with problems of disrespect for academic integrity, to elaborate official recommendations, to stimulate students to respect for academic integrity. The article is of great interest for pedagogical staff, officials, students and anybody interested in this topic.